2019
DOI: 10.1016/j.regen.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix bound nanovesicle-associated IL-33 activates a pro-remodeling macrophage phenotype via a non-canonical, ST2-independent pathway

Abstract: The regenerative healing response of injured skeletal muscle is dependent upon an appropriately timed switch from a local type-I to a type-II immune response. Biologic scaffolds derived from extracellular matrix (ECM) have been shown to facilitate a macrophage phenotype transition that leads to downstream site-appropriate functional tissue deposition and myogenesis. However, the mechanisms by which ECM directs the switching of immune cell phenotype are only partially understood. Herein, we provide the first ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…Several proteases can increase the activity of full-length IL-33 by cleaving off the nuclear localization domain and chromatin binding motif ( 154 , 156 ). We have also recently demonstrated that bio-active IL-33 is present in vesicles bound to the ECM of stromal cells where it is protected from proteolytic modification ( 157 ).…”
Section: Regulatory and Reparative Damps And Specialized Pro-resolvinmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteases can increase the activity of full-length IL-33 by cleaving off the nuclear localization domain and chromatin binding motif ( 154 , 156 ). We have also recently demonstrated that bio-active IL-33 is present in vesicles bound to the ECM of stromal cells where it is protected from proteolytic modification ( 157 ).…”
Section: Regulatory and Reparative Damps And Specialized Pro-resolvinmentioning
confidence: 99%
“…Numerous immune cells express varying levels of ST2. These include basophils, mast cells, eosinophils, group 2 innate lymphoid cells (ILC2s) ( 154 ), CD8 + ( 159 , 160 ), and CD4 + T cells ( 161 ), particularly Th2 cells and Treg ( 74 77 , 158 , 162 ), B cells ( 163 ), macrophages ( 78 , 157 , 163 ), and DC subsets ( 162 , 164 , 165 ). IL-33 acts on these cells to support type 2 responses dominated by the cytokines IL-5 and IL-13.…”
Section: Regulatory and Reparative Damps And Specialized Pro-resolvinmentioning
confidence: 99%
“…For example, will modulating the early inflammatory response or mitigating fibrotic pathways in VML injuries, or both, improve muscle regeneration and functional outcomes? A better understanding of these mechanisms is a prerequisite to the design of more efficacious regenerative therapeutics for VML repair [8,9,[21][22][23][24][25].…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…The location of EVs within the ECM can also dictate certain physiological processes such as differentiation and angiogenesis ( 21 ). During skeletal regeneration, matrix-bound EVs guide macrophage differentiation and downstream myogenesis of skeletal muscle progenitor cells ( 22 , 23 ). EVs can also be freely shed to travel through interstitial fluid to the lymph nodes or diffuse into the bloodstream ( 24 ).…”
Section: Introduction To Extracellular Vesicle (Ev) Biologymentioning
confidence: 99%